Unravelling the Motivations behind Students’ Academic Migrations in Nepal: A Mixed-methods Approach - Aryal, Pitambar; Karki, Tej Bahadur; Mahat, Dipak; Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2024)
Background: Academic migration in Nepal is a complex phenomenon influenced by various factors that impact students’ decision-making processes. Policymakers and educators need to understand these motivations. Methodology: This study investigates why Nepalese students are increasingly choosing to pursue academic opportunities abroad, and domestically. Using a mixed-methods approach, a cross-sectional time horizon was adopted in the Gulmi district of Lumbini province, Nepal. Results: Results show that factors like educational quality, educational opportunities, and career opportunities play a role in motivating academic migration; there is not a significant association between domestic and international academic migration plans with their educational purpose (p = .681), and with career purposes (p = .426). KII and FDG highlighted the lack of learning and earning schemes, demanded courses, technical training for practical courses, career opportunities, and job opportunities for students forced to migrate. Conclusion: The studies on academic migration highlight the complex factors driving students to seek education abroad, including attitudes towards staying in the host country, socio-economic and psychological impacts, and better career prospects. Economic considerations are a primary motivator, with personal attitudes and social networks also influential. For Nepalese students, interest in international migration is driven by perceived better quality of education, extra-curricular opportunities, and political stability. Chi-Square tests show no significant difference in migration plans based on educational or career purposes, indicating similar motivations for domestic and international migrants. Novelty: The study’s strength is in identifying the multifaceted reasons behind students’ decisions to migrate, which include economic, social, and personal factors. It highlights the role of students’ attitudes as a mediator in their migration decisions, a nuanced aspect not widely explored in previous research. Furthermore, the Nepalese context provides a unique perspective on how local conditions and perceptions of opportunities abroad shape migration trends.